Mitochondrial DNA Copy Number Alteration in Human Cancers - Meng, Shasha; Han, Jiali (North American Journal of Medicine and Science, 2013)
Mitochondrial DNA (mtDNA) lacks protective histone and comprehensive DNA repair pathways. To compromise the damage, mitochondria increase their DNA copy numbers. Although the mechanism has not been completely understood, mtDNA copy number alteration has been demonstrated to affect multiple aspects of malignant cells’ behavior. Abnormalities of mtDNA content have also been observed in various human cancers. Moreover, epidemiological studies have showed that the blood mtDNA copy number alteration is associated with the risk of several cancers. The purpose of this review is to briefly introduce several characteristics of mtDNA copy number and its potential role as a diagnostic and prognostic marker for cancer risk prediction and prevention.